Dry Deposition from Sahara Sources Regions of Western Africa. (17th March 2014) - Douaiba, B.; Azzi, A.; Khorsi, A.; Benlefki, A.
Abstract : Sahara dust storms during March 2004 have attracted much attention from the dust-research community due to their intensity, wide coverage, and endurance. In the present work, the dry deposition mechanisms of mineral dust are analysed during an event on the 3 March 2004 over the Northwest African coast. This particular case was chosen based on the strong dry removal that occurred, rendering it ideal for examining the deposition processes. The simulation of synoptic conditions and dry deposition of four dust particles including clay, small silt, large silt, and sand was performed with Eta model, coupled with a desert dust cycle module. The results have been compared with surface data from weather stations in North Africa, data of dry metals from stations located in Gran Canaria, and various satellite images such as European Organization for the Exploitation of Meteorological Satellites and Moderate Resolution Imaging Spectroradiometer for the period in question.